USE OF MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING COMPUTER SCIENCE IN TECHNICAL SCHOOLS (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the theoretical and practical aspects of applying modern pedagogical technologies in teaching informatics in technical colleges. It analyzes the development of students’ information and communication competencies, independent thinking, problem-solving abilities, and practical skills through the introduction of innovative approaches into the educational process.The study is based on foreign pedagogical experiences, including John Dewey’s ideas of experiential learning, Lev Vygotsky’s social constructivist approach, and Benjamin Bloom’s taxonomy, in order to explore ways of improving teaching effectiveness. In addition, the role of methods such as STEM education, Project-Based Learning (PBL), Collaborative Learning, and Gamification in teaching informatics is substantiated.Furthermore, the advantages of using platforms like Google Classroom and Moodle in creating a modern digital learning environment are analyzed. The research findings demonstrate that the use of modern pedagogical technologies enhances the effectiveness of teaching informatics, increases students’ learning engagement, and contributes to preparing them as competent specialists who meet the demands of the modern digital society.